Futures Research on Environmental Sustainability Reporting Model Considering Accountants’ Behavioral Biases - Ramazani Yasuj, Seyed Hamid; Jafari Dehkordi, Hamid Reza; Banitalebi Dehkordi , Bahareh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The objective of this study is to identify and evaluate the impact of behavioral biases on environmental sustainability reporting, with a specific focus on how these biases affect the quality and transparency of reporting. Methodology: This research employs a mixed-methods approach, combining the fuzzy Delphi method and structural equation modeling (SEM). Initially, six behavioral biases influencing environmental sustainability reporting were identified using the fuzzy Delphi method. These biases were then ranked using the Copeland method. The study further validated the proposed model through confirmatory factor analysis (CFA) and structural equation modeling to assess the reliability and validity of the identified biases and their impact on environmental sustainability reporting. Findings: The study identified six key behavioral biases—managerial inflexibility, narcissism, short-sightedness, optimism (two cases), and overconfidence—affecting environmental sustainability reporting. The Copeland ranking revealed that managerial short-sightedness has the most significant negative impact on the quality of environmental sustainability reporting. The findings also showed that these biases contribute to distortions, superficial reporting, and reduced transparency in sustainability reports. The proposed model demonstrated strong convergent validity and reliability through CFA and SEM analysis. Conclusion: The research concludes that behavioral biases, particularly managerial short-sightedness, significantly reduce the quality and transparency of environmental sustainability reporting. The study emphasizes the need for regulatory bodies and accounting standard-setters to develop frameworks that limit the influence of managerial biases on reporting practices. It also suggests that accountants and analysts should be aware of these biases when evaluating the quality of sustainability reports.